Moving to a consumption-based tax system: a quantitative assessment for Brazil - Marcelo Rodrigues dos Santos (Revista Brasileira de Economia, 2010)
For many years, it has been a primary issue in tax policy whether the tax system ought to be built around income tax or consumption tax. Much of the interest in tax policy arises from the widespread belief that taxes on income and savings tend to lower long-run income by retarding the creation and expansion of firms and by discouraging workers and investments. Following this belief, Brazilian government has proposed a tax reform which, basically, replaces tax on investment and labor with tax on consumption. In this paper, we develop a dynamic general equilibrium model with heterogeneous agents to guide our quantitative assessment of the economic and distributional implications of such tax reform. The model is calibrated in such a way that it matches some selected features of the Brazilian economy. We also use the calibrated model to calculate the deadweight loss of each type of taxation and thus provide some rationality for that rearrangement in the tax system. The main result of the paper is that, even though the tax reform increases the asset accumulation, labor and output of economy, it also raises the welfare inequality as borrowing constrained individuals cannot take advantage of the drop in tax on savings. Uma importante questão em política tributária é se o sistema de tributação deve ser construído com foco na taxação da renda ou do consumo. Muito do interesse em política tributária vem da disseminada crença que as taxas sobre a renda e a poupança tendem à reduzir o produto de longo prazo, retardando a criação e a expansão das firmas e desencorajando a oferta de trabalho e o investimento. Seguindo essa idéia, o governo brasileiro propôs uma reforma tributária a qual, basicamente, substitui a taxação do investimento e do trabalho pela taxação do consumo. Nesse artigo, nós desenvolvemos um modelo dinâmico de equilíbrio geral com agentes heterogênios para investigar quantitativamente os efeitos econômicos e distributivos de tal reforma. O modelo é calibrado de forma a reproduzir selecionadas estatísticas da economia brasileira. Nós também usamos o modelo calibrado para calcular a perda de peso morto causada por cada tipo de tributação, o que permite analisar a racionalidade da mudança do sistema tributário proposta pelo governo. O principal resultado do artigo é que, embora a reforma tributária aumente a acumulação de capital, o emprego e o produto da economia, ela também aumenta a desigualdade, uma vez que, além da redução da regressividade do sistema, os indivíduos com baixa renda e que enfrentam restrição à crédito não se beneficiam da redução da taxação da poupança.